Effectiveness Measures According to Lean Management: Empirical Verification of The Concept in The Area of Physical Flows of Production Logistics - Nicoletta BASKIEWICZ (Communications of International Proceedings, 2022)
The aim of the article is both theoretical and empirical recognition of the issues related to physical flows that accompany production processes. The article identifies the types of flows carried out in the enterprise, then focuses on the definition of the physical flows themselves. It shows what influences their effectiveness. In the empirical part, a case study was presented in which a research procedure was conducted aimed at the procedure of verification of the process of physical flows in a friendly company from the tailoring industry. Moreover, an attempt was made to identify the measures that are important from the point of view of managing the optimization of these measure
Keywords: Lean management; production logistics; physical flows; performance measures.